The incarnate Word perspectives on Jesus in the fourth gospel - Thompson, Marianne Meye (Peabody, MA Hendrickson, 1988)
Includes bibliographical references and indexes.
Keywords: Bible. N.T. John -- criticism, interpretation, etc; Bible. N.T. John -- Jesus Christ